Anion and cation substitution in transition-metal oxides nanosheets for high-performance hybrid supercapacitors. (March 2019) - Li, Jinghua; Liu, Zaichun; Zhang, Qiaobao; Cheng, Yong; Zhao, Bote; Dai, Shuge; Wu, Hong-Hui; Zhang, Kaili; Ding, Dong; Wu, Yuping; Liu, Meilin; Wang, Ming-Sheng
Abstract: Anion and cation substitution is an effective way in modulating electrochemical properties of electrode materials to achieve enhanced performance. Herein, we report our finding in the fabrication of advanced binder-free supercapacitor electrodes of hierarchical anion- (phosphorus-) and cation- (zinc- and nickel-) substituted cobalt oxides (denoted as ZnNiCo-P) architectures assembled from nanosheets grown directly on Ni foam. In contrast to the reference Co-P systems, the as-prepared electrode manifests a markedly improved electrochemical performance with a high specific capacity of 958 C g −1 at 1 A g −1 and an outstanding rate capability (787 C g −1 at 20 A g −1 ) due to its compositional and structural advantages. Density functional theory calculations confirm that the Co species partially replaced by Zn/Ni and O species by P can simultaneously improve the charge transfer behavior and facilitate the OH - adsorption and deprotonation/protonation reaction process. Moreover, an aqueous hybrid supercapacitor based on self-supported ZnNiCo-P nanosheet electrode demonstrates a high energy density of 60.1 Wh kg −1 at a power density of 960 W kg −1, along with a superior cycling performance (89% of initial specific capacitance after 8000 cycles at 10 A g −1 is retained). These findings offer insights into the rational design of transition metal compounds with multi-components and favorable architectures by manipulating the cations and anions of metal compounds for high-performance supercapacitors. Graphical abstract: A high-performance mix-metal phosphide nanosheet electrode enables excellent capacity, rate capability, and cycle stability of hybrid supercapacitors. The electrode is composed of hierarchical Zn and Ni co-substituted Co phosphide nanosheet arrays grown on porous Ni foam. fx1 Highlights: Hierarchical ZnNiCo-P nanosheet arrays grown directly on Ni foam are constructed for the first time. The resultant binder-free electrodes manifest outstanding electrochemical performances. The synergetic contribution and structural features together contribute to outstanding electrochemical performance. The assembled ZnNiCo-P//PPD-rGOs hybrid supercapacitor achieved a high energy density of 60.1 W h kg −1 at a power density of 960 W kg −1 .